Building EXCITEment for Vaccines in Rural Communities. - Rodgers, Michelle S.; Downey, Laura H.; Gregory, Tia M.; Austin, Erica Weintraub; Burton, Dawn E.; Clark, Laura; Hursman, Ruth; Peters, Paula; Stofer, Kathryn A.; Wilkins, Jacqueline; DeWald, Erica L. (American Journal of Public Health, 2025)
The Cooperative Extension System (CES) consists of 112 land-grant universities in the United States, including historically Black universities and Tribal colleges. In 2021, CES formed the Extension Collaborative on Immunization Teaching and Engagement (EXCITE) to increase confidence in and access to adult immunizations. From April 2021 to May 2023, EXCITE conducted 111 immunization education projects involving 76 land-grant universities. EXCITE reached more than 18 million individuals, and more than 48 000 COVID-19 and other adult-recommended vaccines were provided in partnership with local health organizations.